Kinerja Auditor ditinjau dari Independensi, Konflik Peran dan Budaya Organisasi - Trisya Noer Octavia; Putri Robiatus Saada; Waras (Kampus Akademik Publiser, 2024)
This study is a quantitative study conducted to determine the effect of independence, role conflict and organizational culture partially or simultaneously on the performance of Public Accounting Firm auditors in the city of Surabaya. The population in this study were all auditors who worked at 21 Public Accounting Firms. (KAP) in Surabaya with a total sample of 110 respondents. The sample selection technique used was purposive sampling method and was tested using multiple linear regression analysis with SPSS test tools. The source of data used in this study is primary data from a survey with a questionnaire. From the results of the analysis that has been carried out, this study shows that the variables of independence, role conflict, and organizational culture have a significant partial or simultaneous effect on the performance of the Public Accounting Firm auditor in the city of Surabaya. The results of the simultaneous test showed a significance value of F of 0.000 <0.05 of the probability value. The variables of independence, role conflict, and organizational culture are able to influence the performance of auditors with a coefficient of determination of 0.402 or 40.2% on the performance of Public Accounting Firm auditors in the city of Surabaya.